An anticorrelation between barycentre offsets and velocity dispersion for highest overdensity subhaloes in cosmological simulations. Issue 4 (4th July 2018) - Li, Ming-Hua; Lin, Hai-Nan
ABSTRACT: In this paper, we use two hydrodynamic simulations to study the barycentre offsets r off between the entire halo and the gas or dark matter subhalo with largest overdensity. We restrict our analysis to those haloes with large rescaled offsets, i.e. r off / r 200 ≳ 0.05. The haloes which are less massive and at higher redshifts are more likely to have larger r off / r 200 . The 3D velocity dispersion of the subhaloes with largest overdensity is found to have a similar mass and redshift dependence as r off / r 200 . We also find that the gas subhaloes with maximum overdensity and larger gas velocity dispersion $\sigma _{v}^{\rm ICM, sub}/\sigma _{200}$ tend to have smaller barycentre offsets r off / r 200 . Similar result is found for the highest overdensity dark matter subhaloes but with less significance. This anticorrelation is more significant for the snapshot z  = 0 than z  = 0.2 and 0.5. The underlying physical mechanism for this anticorrelation remains to be explored.